2009
DOI: 10.1029/2008ja013782
|View full text |Cite
|
Sign up to set email alerts
|

Polarization and phase of planetary‐period magnetic field oscillations on high‐latitude field lines in Saturn's magnetosphere

Abstract: We examine magnetic field data obtained by the Cassini spacecraft on a sequence of high‐latitude orbits in Saturn's magnetosphere spanning October 2006 to May 2007 to determine whether planetary‐period oscillations are present on polar open field lines, such as have been found previously in near‐equatorial magnetic field data. Such oscillations are found generally to be present with amplitudes ∼0.5–1 nT, somewhat smaller than the few nT amplitudes typical of the quasi‐dipolar equatorial region. The polarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
269
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 87 publications
(313 citation statements)
references
References 41 publications
(133 reference statements)
43
269
1
Order By: Relevance
“…The polarization characteristics of the purely northern and purely southern PPOs are described in Table 1, which also presents, γ i S,N , the difference in phase between the r component and component i, where i = r, θ, and φ, such that by definition γ r S ≡0°and γ r N ≡0°. For further explanation of the polarization of the northern and southern oscillations, see Provan et al [2009a].…”
Section: 1002/2015ja021642mentioning
confidence: 99%
See 1 more Smart Citation
“…The polarization characteristics of the purely northern and purely southern PPOs are described in Table 1, which also presents, γ i S,N , the difference in phase between the r component and component i, where i = r, θ, and φ, such that by definition γ r S ≡0°and γ r N ≡0°. For further explanation of the polarization of the northern and southern oscillations, see Provan et al [2009a].…”
Section: 1002/2015ja021642mentioning
confidence: 99%
“…The first PPO transition time demarked the start of interval E2 in the old nomenclature. Before this time the periods and the phases were believed to change slowly over time as presented in Andrews et al [2008] and Provan et al [2009a]. We here define this first PPO transition as boundary 1, with interval 1 spanning the time period just prior to the 2009 equinox until boundary 1.…”
Section: Magnetic Field Oscillations In the Postequinox Intervalmentioning
confidence: 99%
“…During the interval of interest here spanning 2008, occurring somewhat before Saturn equinox in mid-August 2009, the northern and southern periods were well separated at~10.60 and 10.82 h, respectively. At a given point in the equatorial region inside the main field-aligned current sheets the azimuthal field of each system thus oscillates in lagging quadrature with the radial component, this being the signature of a quasi-uniform perturbation field in the near-equatorial region, while outside the current sheets the sense of the azimuthal field is reversed so that it oscillates in leading quadrature with the radial, this being the signature of a quasi-dipolar field [Espinosa and Dougherty, 2000;Espinosa et al, 2003;Cowley et al, 2006;Southwood and Kivelson, 2007;Andrews et al, 2008Andrews et al, , 2010aProvan et al, 2009]. The colatitudinal component then oscillates in antiphase with the radial in the northern system and in-phase with the radial in the southern, as is evident in Figures 1e and 1h.…”
Section: Introductionmentioning
confidence: 99%
“…It turned out that many magnetospheric phenomena can be organized around the SKR periodicity. The magnetic field shows similar periodicities (Espinosa and Dougherty, 2000;Andrews et al, 2008, Provan et al, 2009, and southern-northern duality was even discovered in the magnetic field variations , Provan et al 2012. Burch et al (2009) have shown that the heavy (water group) ion population of the Kronian plasma exhibit a cam-like feature (the plasma cam) in a longitude system fixed to SKR.…”
Section: Introductionmentioning
confidence: 66%
“…Another method to find an approximately known periodicity is to apply a band-pass filter to the time series. Andrews et al (2008Andrews et al ( , 2012 and Provan et al (2009Provan et al ( , 2012 used this method. Although the periodicity and its variation is very clear in the filtered data, some information is inevitably lost in the process.…”
Section: Introductionmentioning
confidence: 99%